Analysis Trade Integration of Indonesia and Turkey Non-Oil Sector - Yuliati, Lilis; Atmaja, Purna Pria; Lestari, Endah Kurnia (Universitas Negeri Semarang, 2020)
Development of the economy and improve the world economy which is increasing in the future. This causes an increase in trade in the same sector (Intra-Industrial Trade). In addition, promoting trade that focuses on fluctuating and unstable pushes Indonesia to further enhance its export competitiveness through market diversification, encouraging to minimize export fluctuations towards the main export destination countries. Commitment to a market diversification strategy has made Turkey an alternative export destination. The purpose of this research is to study the great integration of trade and export dynamics in the non-oil sector between Indonesia and Turkey during the period 2001-2016. Analysis using Gruble Lloyd Index (GLI) shows that the intensity of trade between Indonesia and Turkey is more in the category of Weak Integration (Weak Integration). While the analysis of the Constant Market Share (CMS) shows that each period is fluctuating, in the first period, the second period, the second period, the fourth period, the questioning period, the sixth period, the ninth period, the tenth period, and the second positive period, while in the seventh period , the eighth period, the eleventh period, the fourteenth period, and the twelve period of negative export value changes.